Change of Hepatobiliary System under the Influence of Hydrazine Derivatives - Saspugayeva G.Y. (Journal of Global Pharma Technology, 2016)
Hydrazine derivatives are used in different spheres, in aero-space activity, medical practice, laboratory-diagnosis practice, that is why environment is polluted with hydrazines in big areas. The question about influence of hydrazine derivatives, used as the rocket fuel, on the human organism and ways of its detoxication is very actual. In connection with appeared situations, we set the goal: to study the negative influence of hydrazine derivatives-hydrazine sulphur, nitrosodimethylamine (NDMA), phenylhydrazine, isonicotinic acid hydrazide (IAH) on several biochemical features of blood and correction of functional damages of organism with “Salsocollin” preparation.Keywords: Isonicotinic acid hydrazide (IAH), N-nitrosodimethylamine (NDMA), AlAT-alanine aminotransferase, AsAT-aspartate aminotransaminase, Salsocollin.